2023
DOI: 10.1590/1519-6984.246825
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary leaf extracts of Black pepper Piper nigrum L. on the growth, hematological and immunological parameters of Labeo rohita (Hamilton, 1822) cultured in glass aquaria

Abstract: A study was conducted to evaluate the effect of Piper nigrum (black pepper) leaf extract on on the growth performance, proximate composition, hematological parameters, and immune response of Labeo rohita fingerlings with an average weight of 22.14 ± 0.98g. Aftrer acclimation for two weeks, fish (n=25) were randomly selected and placed in four glass aquaria (T0, T1, T2 and T3) at constant water temperature (30.0 ± 1.0 °C), pH (7.50 ± 0.5) and total hardness (200 ± 2.0 mgL,-1) for a period of 12 weeks, with thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In glass aquariums, due to the flat and smooth surface, cleaning is easier and more effective (Ullah et al, 2023), removing the eggs to avoid consumption. In aquariums with ceramic floors, due to porosity (Souza et al, 2008) there is greater adhesion of organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…In glass aquariums, due to the flat and smooth surface, cleaning is easier and more effective (Ullah et al, 2023), removing the eggs to avoid consumption. In aquariums with ceramic floors, due to porosity (Souza et al, 2008) there is greater adhesion of organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…( 61 ) showed that the dietary supplementation of red bell pepper ( Capsicum annum ) at an inclusion level of 44 or 55 mg/kg for 20–60 days significantly increased the BW and total length, but not the SGR in rainbow trout ( Oncorhynchus mykiss ). When supplementing fish diets with black pepper or its extracts, growth was not enhanced in African catfish ( Clarias gariepinus ), rainbow trout, and common carp ( Cyprinus carpio ) ( 62 64 ), but weight gain was significantly increased in rohu fish ( Labeo rohita ) when adding the extract to the diet at an inclusion level of 1% or 2% ( 65 ). Among the four spices tested in the current study, ginger has been the most studied regarding its growth enhancing effect in teleosts ( 66 70 , among others).…”
Section: Discussionmentioning
confidence: 99%
“…( 20 ) when supplementing gilthead seabream diets with 0.1% and 0.15% of this additive during winter. While none of the aforementioned studies testing the effect of capsicum in fish diets described an amelioration of FCR ( 56 , 58 60 ), some of the works with black pepper or ginger and many of those with cinnamaldehyde supplementation did ( 63 , 65 , 66 , 68 , 70 , 72 , 74 , 75 ). Therefore, the decrease in FCR in fish fed the SPICY 0.1% diet might be partly attributed to the active principles of ginger and black pepper and to cinnamaldehyde or to the synergetic effect of the four spices present in the tested product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in this study, supplementation of black pepper showed a slight reduction of plasma hemoglobin and hematocrit compared to Con diet. Ullah et al (2021) showed contradictory results an increase in red blood cells, total leukocyte count and lymphocytes in Labeo rohita with black pepper leaf extract supplementation. Hassan et al (2023) showed that red pepper oil supplementation significantly increased the red blood cells count and hemoglobin in broilers.…”
Section: Fisheries and Aquatic Sciencesmentioning
confidence: 97%